2017
DOI: 10.1371/journal.pmed.1002385
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effectiveness and cost-effectiveness of the Healthy Activity Programme, a brief psychological treatment for depression delivered by lay counsellors in primary care: 12-month follow-up of a randomised controlled trial

Abstract: BackgroundThe Healthy Activity Programme (HAP), a brief behavioural intervention delivered by lay counsellors, enhanced remission over 3 months among primary care attendees with depression in peri-urban and rural settings in India. We evaluated the sustainability of the effects after treatment termination, the cost-effectiveness of HAP over 12 months, and the effects of the hypothesized mediator of activation on clinical outcomes.Methods and findingsPrimary care attendees aged 18–65 years screened with moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 50 publications
3
126
0
Order By: Relevance
“…The community interventions above (Appendix A ), drawn from a larger selection (Appendix B ), highlight the successes and promise of these interventions to promote mental health and broader outcomes at all social-ecological levels: individual, interpersonal/family, organizational/institutional, community, and policy [ 3 ]. Community involvement is represented in varied ways in the form of individuals (lay health workers), settings (churches, schools), leaders (community-based participatory research), and multi-sector coalitions [ 35 •, 37 , 38 , 39 •, 85 •, 86 90 , 91 •, 103 •]. Many studies examined the interplay among mental health services, social and structural determinants, and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The community interventions above (Appendix A ), drawn from a larger selection (Appendix B ), highlight the successes and promise of these interventions to promote mental health and broader outcomes at all social-ecological levels: individual, interpersonal/family, organizational/institutional, community, and policy [ 3 ]. Community involvement is represented in varied ways in the form of individuals (lay health workers), settings (churches, schools), leaders (community-based participatory research), and multi-sector coalitions [ 35 •, 37 , 38 , 39 •, 85 •, 86 90 , 91 •, 103 •]. Many studies examined the interplay among mental health services, social and structural determinants, and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed community interventions in international settings, acknowledging the shared social, structural, and mental health challenges that exist across nations. Many of the reviewed studies involve lay health worker (LHW) interventions [ 85 •, 86 90 ]. Barnett et al in their 2018 review of LHW interventions describe that LHWs elevate demand for services by increasing awareness of services and mental health literacy and by reducing stigma and barriers to care [ 85 •].…”
Section: Global Mental Healthmentioning
confidence: 99%
“…An RCT in India (Patel et al, 2010) showed that a collaborative care intervention led by lay counsellors was cost-saving to the health system (Buttorff et al, 2012). A 6–8 session behavioral activation treatment delivered by lay counsellors in primary health care settings in India was also cost effective, reducing depression and improving functioning in people with moderately severe to severe depression (Patel et al, 2017; Weobong et al, 2017). A systematic review of task-shifting interventions for non-communicable diseases in LMICs showed that it is potentially effective for improving access for mental healthcare (Joshi et al, 2014).…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…Behavioral activation teaches participants to set short-term goals, make detailed plans, and systematically start with the easiest tasks to "get going." This breaks the cycle of avoidance, and harnesses self-reinforcing motivation cycles (Ekers et al 2014;Weobong et al 2017).…”
Section: Treatment 2: Planning + Information Module ("P+inf")mentioning
confidence: 99%